تشخيص بعض فيروسات البطاطا الحلوة باستخدام تقنيتي النباتات الدالة والاختبارات المصلية - إسماعيل عماد; راعي سليم; عاقل إنصاف (Latakia University Journal -Biological Sciences Series, 2018)
تم حصر الأمراض الفيروسية على محصول البطاطا الحلوة في مناطق زراعتها الرئيسية في الساحل السوري خلال موسمي 1200/2002 و 2002/2003. أخضعت عدة عينات أظهرت تفاعلاً مصلياً إيجابياً ضد فيروس البرقشة الريشية وفيروس موزاييك الخيار، للاختبار الحيوي بطريقة العدوى الميكانيكية بالعصارة النباتية، التطعيم على عدد من النباتات الدالة، وذلك بهدف التعرف على بعض النباتات الدالة العائلة لبعض فيروسات البطاطا الحلوة من جهة، وللكشف عن بعض الفيروسات التي تصيب البطاطا الحلوة غير المستخدمة أمصالها في الاختبار من دون تحديد هويتها من جهة ثانية. أظهرت النتائج أن طريقة التطعيم في نقل الإصابة أكثر كفاءة من العدوى بالعصارة النباتية عندما تم تجريب الطريقتين، حيث لوحظ أن أغلب النباتات الدالة المستخدمة بالأعداء بدأت بإعطاء أعراض مختلفة من الموزاييك ، الاصفرار، تشوه الأوراق والتقزم وذلك بعد فترة تراوحت من أسبوعين إلى ثلاثة أسابيع من الإعداء. أكدت النتائج على إمكانية نقل فيروس البرقشة الريشية بالتطعيم من النباتات المصابة إلى كل من النباتات الدالة التالية Nicotiana. benthamiana، Nicotiana. tabacum Var. samsun، I. nil، I. setosa، Chenopodium quinoa ، وإمكانية نقل فيروس موزاييك الخيار بالتطعيم أيضاً إلى كل من النباتات Nicotiana. glutinosa، N. benthamiana، N. tabacum (w.b) لذلك تعتبر هذه النباتات نباتات دالة للكشف عن هذين الفيروسين في حال الأعداء بالتطعيم، كما لوحظ تباين في أعراض الإصابة الظاهرية على بعض النباتات الدالة مثل نبات Ipomoea setosa باختلاف العقل من البطاطا الحلوة المصابة بفيروس البرقشة الريشية والمستخدمة في التطعيم، وهذا قد يشير إلى وجود سلالات أو عزلات مختلفة للفيروس في المنطقة. A survey of sweet potato viral diseases in the main cultivating areas of Syrian costal region was conducted during 2001/2002 and 2002/2003 growing seasons. Different symptoms of sweet potato samples showed positive infection with sweet potato feathery mottle potyvirus (SPFMV) and Cucumber mosaic cucumovirus (CMV). The same samples submitted to sap mechanical transmission, and graft transmission on different indicator plants to determine the host range among indicator plants, and to detect some sweet potato viruses other than these detected by used antesera. Results showed that virus graft transmission was more efficient that sap mechanical transmission when these two methods were evaluated. All plants showed various degree of mosaic, chlorosis, leaf malformation, and stunting symptoms, two to three weeks post-graft inoculation. Sweet potato feathery mottle potyvirus is graft-transmissible from infected samples to N. tabacum (sn), N. benthamiana, I. setosa, I. nil, Chenopodium quinoa. Cucumber mosaic cucumovirus also graft-transmissible to N. glutinosa N. benthamiana N. tabaccum (w.b), but it is not mechanically sap-transmissible. So it is possible to consider these plants as indicators of these two viruses in graft inoculation case. Moreover, different viruses symptoms on the same indicator plants were observed, as I. setosa, when these plants were grafted by different sweet potato scion infection with Sweet potato feathery mottle potyvirus (SPFMV). This result is new, and it is possible that different strains of sweet potato feathery mottle potyvirus (SPFMV) are present in region.